The Eye of the Common Octopus (Octopus vulgaris) - Hanke, Frederike D.; Kelber, Almut (Frontiers in Physiology, 2020)
Octopus vulgaris, well-known from temperate waters of the Mediterranean Sea and a well-cited model species among the cephalopods, has large eyes with which it scans its environment actively and which allow the organism to discriminate objects easily. On cursory examination, the single-chambered eyes of octopus with their spherical lenses resemble vertebrate eyes. However there are also apparent differences. For example, the retina of the octopus is everted instead of inverted, and it is equipped with primary rhabdomeric photoreceptors rather than secondary ciliary variety found in the retina of the vertebrate eye. The eyes of octopus are well adapted to the habitat and lifestyle of the species; the pupil closes quickly as a response to sudden light stimuli mimicking a situation in which the octopus leaves its den in shallow water during daytime. Although the many general anatomical and physiological features of octopus vision have been described elsewhere, our review reveals that a lot of information is still missing. Investigations that remain to be undertaken include a detailed examination of the dioptric apparatus or the visual functions such as brightness discrimination as well as a conclusive test for a faculty analogous to, or in lieu of, color vision. For a better understanding of the octopus eye and the functions mediated by it, we suggest that future studies focus on knowledge gaps that we outline in the present review.